Iñupiatun Eskimo Dictionary - Seiler, Wolf A. (SIL International, 2005)
http://www.sil.org/resources/archives/43482 The Iñupiatun (Eskimo) language represents one of the western-most languages of the Inuit (Eskimo) language continuum. Inuit is spoken by about 120,000 people between East Greenland and northern Alaska. The words in this dictionary were collected in a period of roughly forty years. Principal collectors were Wilfried Zibell (†1971) and Wolf Seiler, both affiliated with the Summer Institute of Linguistics (SIL), and the latter prepared the collection for publication in 2004. The collection contains more than 10,000 words. It lists words alphabetically in Iñupiatun as well as in English. In addition it contains a substantial list of derivational affixes. Finally, there are several appendices, which describe various aspects of grammar and the deictic system. “Words have history. Each definition of a word contains the meaning that speakers assign to it. At the same time, any word contains, metaphorically speaking, the person who speaks it and includes the situation in which the speaking occurs and the reason for speaking it. This collection of words creates for the present Iñupiaq people, therefore, a sense of connectedness to their forefathers and to their way of life and history” (From the preface). [ In the interest of making this work available without further delay, we are posting it as it was written. It has not been subjected to further review.]